Two new species of Trimeria de Saussure from Brazil, with biological notes and a key to the Brazilian taxa (Hymenoptera, Vespidae, Masarinae) - Hermes, Marcel G.; Melo, Gabriel A.r. (Zootaxa, 2006)
Two new species of the masarine genus Trimeria de Saussure are described from Brazil: T. robusta new species, from Minas Gerais and Bahia, and T. rubra new species, from Rondônia. Anecdotal information on nests of T. robusta is presented. A key to the identification of the Brazilian species is provided.